The association between dietary inflammatory index and cognitive function in adults with/without chronic kidney disease - Wan, Biyu; Lin, Pinli; Wang, Mengya; Zhong, Jintao; Peng, Lu; Tang, Xiaona; Wang, Lingzhen; Tang, Fang; Liang, Yuyan; Liu, Xusheng; Deng, Lili (Frontiers in Nutrition, 2023)
Background and Aims: Cognitive impairment (CI) is a prevalent condition in patients with chronic kidney disease (CKD), who face an elevated risk of developing cognitive decline. The fundamental mechanism underlying CI is linked to chronic inflammation, which can be gauged by the Dietary Inflammatory Index (DII). The DII is categorized into anti-inflammatory diets with lower scores and pro-inflammatory diets with higher scores. Specifically, pro-inflammatory diets may contribute to chronic inflammation. However, the correlation between the inflammatory potential of diet and cognitive function in patients with CKD has not been explored. This study aims to investigate the connection between the inflammatory potential of diet and cognitive function in individuals with or without chronic kidney disease.